2012
DOI: 10.3892/or.2012.1772
|View full text |Cite
|
Sign up to set email alerts
|

Allicin inhibits cell growth and induces apoptosis in U87MG human glioblastoma cells through an ERK-dependent pathway

Abstract: Abstract. Allicin, the main flavor compound in garlic, has anti-carcinogenic activities in a range of cancer cells, however, the underlying molecular mechanisms are not completely understood. This study examined the effect of allicin on the cell viability of U87MG human glioma cells along with its molecular mechanisms of induction of cell death. Apoptosis was determined by TUNEL and Hoechst 33258 staining as well as by western blot analysis. Allicin inhibited the cell viability of U87MG human glioma cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In combination, the results showed that capsaicin induced apoptosis in the MG63 cells and that the caspase cascade and antioxidant enzyme system were the underlying regulatory signaling pathways involved in the capsaicin-induced apoptosis. In a previous study, we demonstrated the effect of capsaicin on human glioblastoma U87MG cells and concluded that capsaicin induced apoptosis in the U87MG cells ( 62 ). The present results indicated that capsaicin exhibited an anticancer effect in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…In combination, the results showed that capsaicin induced apoptosis in the MG63 cells and that the caspase cascade and antioxidant enzyme system were the underlying regulatory signaling pathways involved in the capsaicin-induced apoptosis. In a previous study, we demonstrated the effect of capsaicin on human glioblastoma U87MG cells and concluded that capsaicin induced apoptosis in the U87MG cells ( 62 ). The present results indicated that capsaicin exhibited an anticancer effect in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…For example, it was reported that miltefosine-induced GBM cell apoptosis is dependent on ERK1/2 activation [ 42 ]. Similarly, allicin-induced apoptosis is regulated by MAPK/ERK-dependent pathway [ 43 ]. In our hands, IL-22 treatment promotes GBM cell proliferation and protects them from apoptosis via the phosphorylation of STAT3, Akt and inactivation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Allicin has been found to inhibit the cell viability of U87MG human glioma cells and induce cell death through apoptosis. This allicin-induced apoptosis was mediated through Bcl-2/Bax mitochondrial pathway, MAPK/ERK signalling pathway and antioxidant enzyme systems [ 28 ]. Study on the effect of allicin on the growth of human liver cancer Hep G2 cells showed that allicin induced p53-mediated autophagy and inhibited the viability of human hepatocellular carcinoma cell lines.…”
Section: Sulphur Compoundsmentioning
confidence: 99%
“…Mechanistically it was demonstrated that allicin stimulates the JNK pathway activation, which ultimately results in mitochondrial translocation of Bax and release of cytochrome C from mitochondria to cytosol, thus inducing the apoptosis of SKOV3 cells [ 65 ]. A subsequent study suggested that allicin might inhibit the cell viability and induce apoptosis in U87MG glioblastoma cells via regulating the Bac/Bcl2 and MAPK/ERK signalling pathways [ 28 ]. The other compound called ajoene, the organo-sulphur compound of garlic, has also been reported to induce apoptosis in the human promyeloleukaemic cell line (HL-60) through the generation of reactive oxygen species (ROS).…”
Section: Biological Activities Of Sulfur Compounds From mentioning
confidence: 99%